2017
DOI: 10.1007/s13224-017-1079-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Copper Device (CuT380A) as a Contraceptive Method in the Indian Context: Acceptability, Safety and Efficacy Depending on the Timing of Insertion

Abstract: IUCD was more acceptable among young, literate and multiparous women as a contraceptive method. Immediate postpartum period was the safest and most efficacious time for IUCD insertion with least expulsion rate, maximum continuation rate and no failure and, therefore, should be encouraged by adequate counseling of mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Thiery et al reported that more the expertise lower were the expulsions rates, although definition of skill level was not given. 14,15 IUDs in the immediate post-partum period have higher expulsion in when compared to interval insertions. Mostly the women with expulsion use another or same technique for contraception to avoid accidental pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…Thiery et al reported that more the expertise lower were the expulsions rates, although definition of skill level was not given. 14,15 IUDs in the immediate post-partum period have higher expulsion in when compared to interval insertions. Mostly the women with expulsion use another or same technique for contraception to avoid accidental pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…Pelvic infection was diagnosed if women had cervical, adnexal, or uterine tenderness or purulent discharge with or without fever. 7 postpartum IUCD insertions in a study by Poornima et al 13 Pain abdomen was noted in only one case which could be treated with simple analgesics. This shows that significant abdominal pain is not seen in intra-caesarean IUCD insertion.…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Urmila et al, continuation of PPIUCD was observed in 76.5% cases. 14 The removal rate of CuT380A was higher in the postpartum group (7.56%) than in interval group (4.37%) in a study by Poornima et al 13 Continuation of intra-caesarean PPIUCD for at least 6 months effectively postpones pregnancy by 1 year while use for at least one year reduces pregnancy rate by one third.…”
Section: Discussionmentioning
confidence: 95%
“…Safe and effective contraception is part of quality contraceptive treatment for all women of reproductive age [ 8 ]. Copper IUCDs are an efficient technique for limiting fertility as it is a non-hormonal, safe, quickly reversible, low-cost, very successful, long-lasting (Copper T 380A (CuT380A) has a life span of 10 years) method of contraception.…”
Section: Discussionmentioning
confidence: 99%